EFFECT OF WORK-LIFE BALANCE, COMPENSATION, AND ENGAGEMENT ON TEACHER PERFORMANCE IN SOUTH TANGERANG - N. Lilis Suryani; Aida Vitayala Sjafri Hubeis; Widodo Sunaryo (International Journal of Economy, Education and Entrepreneurship, 2021)
This study aims to analyze the effect of work-life balance, Compensation, and engagement on the performance of high school teachers in the South Tangerang area. The Collected data by sending questionnaires to 113 high school teachers in the South Tangerang area. This research uses quantitative methods and SmartPLS 3.0 software to evaluate the outer and inner models. This study leads to the conclusion that work-life balance improves teacher performance.Teacher performance improves as a result of Compensation.Teacher performance improves when employees are engaged.